Impact of chickpea aquafaba-based emulsion on the physicochemical, nutritional, rheological and structural characteristics of little millet (Panicum sumatrense Roth.) flour cake - Madhavi B.; Asaithambi N.; Kumar A.; Maiti P.; Rai D.C.; Duary R.K. (My University, 2025)
Recent patterns in food consumption indicate that consumers have a strong desire for vegan, gluten-free,and healthy diets. This study investigates the utility of chickpea aquafaba and little millet flour (LMF) asalternatives to egg and refined flour, respectively, for developing egg-free and gluten-free cake recipes.The cake and batter were analyzed for their physicochemical, structural, sensorial, rheological andtextural properties, with a shelf-life study conducted over a period of 12 days (30 ± 2 °C). The batter'sdensity (1.13 ± 0.01 g cm−3) and viscosity (15796.7 ± 0.09 cp) increased with the addition of LMF, andthe batter predominantly exhibited an elastic behavior with G0 > G00 for all cake formulations. Thesecharacteristic changes in cake batter caused the cake's weight to increase (by 10%) while causing itsheight, baking loss, volume, specific volume and symmetry index to decrease. The texturalcharacteristics showed that adding LMF to cakes enhanced the hardness (145.00 ± 9.45 N) and firmness(19.36 ± 2.12 N) and decreased their cohesion, chewiness, gumminess, springiness and resilience. Theimage analysis showed more uniform bubble distribution in wheat flour (WF) cake than in LMF cakes, andan increase in LMF content resulted in a drop in cell circularity. The microbial degradation of cakes wasobserved from the 6th day of storage. LMF cake samples exhibited good texture and physical andsensory attributes comparable to those of the WF cake sample. Therefore, the study demonstrated thepotential use of alternative ingredients, such as LMF and aquafaba emulsion, in the production of eggfree and gluten-free cakes. These ingredients could facilitate the scaling up of sustainable productionpractices for baked goods in the future. © 2024 Royal Society of Chemistry. All rights reserved.